Alcohol and Gastric Motility: Pathophysiological and Therapeutic Implications. (June 2020) - Gonzalez, Zorisadday; Herlihy, Daniel; Phan, Cong; Diaz, Jesus; Dominguez, Kenneth; McCallum, Richard
Alcohol has been associated with alterations in gastric motility. The literature identifies that various factors play a role in alcohol's effect on gastric emptying including differences in alcohol concentration, osmolarity, caloric content, amino acids as well as different processing techniques (fermentation vs distillation). Additionally, chronic alcohol consumption has been shown to alter the myenteric nitrergic system resulting in impaired gastrointestinal motor function, and it also has an inhibitory effect on the release of several neurotransmitters that play a key role in gastrointestinal motility, including acetylcholine. Whether social or limited intake of alcohol could have a therapeutic role has not been apparent. Serendipitously, we have identified a therapeutic role for alcohol with a meal in the entity of dumping syndrome (DS) where there is postprandial rapid emptying of voluminous and hyperosmolar gastric contents into the small bowel. In the clinical setting of DS attributed to impaired vagal nerve function, there was normalization of gastric emptying and resolution of accompanying symptoms when drinking a glass of wine before and during meals. We propose that alcohol's anticholinergic effect was augmented in the setting of vagal nerve denervation resulting in slowing of gastric emptying and in alleviation of symptoms of early DS. This review article provides an in-depth analysis of the published literature on alcohol and gastric motility focusing on the accumulated knowledge that may have clinical application and relevance.